(untitled) (Journal of Pharmaceutical Negative Results, 2022)
An essential component for encoding and decoding numbers is a reversible priority encoder, which is designed in this study. Binary-coded decimal (BCD), a promising nanotechnology, may provide a framework for reversible circuit implementation. This work proposes a simple BCD platform-based bidirectional 4 to 2 prioritized decoder design. The low-cost Toffoli gate design is suggested for use in reversible encoder circuit implementation. The suggested designs are assessed structurally using the BCD Designer simulation.